A Systematic Approach to Patients with Elevated Levels of Serum Amylase or Lipase - Seong Ji Choi (The Korean Journal of Gastroenterology, 2023)
Serum amylase and lipase tests are routinely performed in patients presenting with abdominal pain or even during regular health screening. Elevated serum levels of these two enzymes are often encountered in clinical practice. The differential diagnosis is broad and includes acute pancreatitis, chronic pancreatitis, gastrointestinal tract obstruction, malignancies, and other disease conditions. In this article, we review the pathophysiology of elevated amylase and lipase, possible conditions that cause the increase, and diagnostic strategies for such patients. We conclude that a systematic approach to patients with elevated amylase and/or lipase is critical to making an accurate diagnosis and initiating appropriate treatment.